2021
DOI: 10.1007/s40195-021-01209-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Strength–Ductility Balance of the Laser Melting Deposited 12CrNi2 Alloy Steel Via Multi-step Quenching Treatment

Abstract: A ferrite-austenite 12CrNi2 alloy steel additively manufactured by laser melting deposition (LMD) was heat treated by direct quenching (DQ) and tempering inter-critical quenching (TIQ) at 800 °C for enhancing its strength-ductility balance. Both heat-treated alloy steels have the martensite-ferrite dual-phase (DP) microstructures. The volume fractions of martensite in the two treated alloy steels are nearly similar (~ 85 vol%), while the sizes of the prior austenitic grain for martensite are different. The mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…During heating and isothermal holding at 800°C, austenite is formed by the decomposition of martensite. The austenitic grains easily grow in the process and transform into the polygonal-like lath martensite (Figure 5(d)) after the IQ treatment [30]. As for the G3 and G5, there is no obvious change in the microstructure after heat treatment compared to G1, and it is characterised by finer microstructures and more spherical particles after Q-IQ and Q-IQ-T heat treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During heating and isothermal holding at 800°C, austenite is formed by the decomposition of martensite. The austenitic grains easily grow in the process and transform into the polygonal-like lath martensite (Figure 5(d)) after the IQ treatment [30]. As for the G3 and G5, there is no obvious change in the microstructure after heat treatment compared to G1, and it is characterised by finer microstructures and more spherical particles after Q-IQ and Q-IQ-T heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This study revealed that the elongation and the tensile strength of 12CrNi2 were simultaneously increased after the sample was subjected to tempering process. Zhang et al [30] have adopted direct quenching and tempering intercritical quenching at 800°C to LMD 12CrNi2 alloy steel, and revealed that the alloy steel treated by multi-step possessed higher elongation and better ductility. However, the studies on the camshaft materials prepared by LMD after Q-IQ and Q-IQ-T heat treatment are scarcely reported, especially for analysing the relation of microstructure evolution and the performances such as wear and corrosion on a surface with quasi-continuous ratios gradient material.…”
Section: Introductionmentioning
confidence: 99%
“…Other scholars have studied the effects of process parameters and cooling rate on residual stress [ 17 ], indicating that cooling rate and temperature gradient are related to the trend of residual stress. Some researchers have verified that the ferrite-austenitic 12CrNi2 alloy steel manufactured by laser melting deposition (LMD) can enhance its strength–ductility balance after heat treatment [ 18 ]. A study has been well verified that SR could effectively enhance the mechanical properties of the alloy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%